2006
DOI: 10.1038/modpathol.3800533
|View full text |Cite
|
Sign up to set email alerts
|

Malignant mixed tumors of the salivary gland: a study of loss of heterozygosity in tumor suppressor genes

Abstract: Carcinosarcomas and carcinoma ex pleomorphic adenoma of the salivary glands are rare tumors that fit into the broader category of malignant mixed tumors. Although most evidence has suggested that the different morphologic components arise from a common clonal origin, there are very few studies that have provided molecular evidence for this clonality. In this study, we examined a set of seven carcinosarcomas and four carcinomas ex pleomorphic adenoma for tumor suppressor gene loss of heterozygosity, in order to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 17 publications
2
28
1
Order By: Relevance
“…Studies have suggested that cxpa follows a multistep model of carcinogenesis, with progressive loss of heterozygosity at chromosomal arm 8q, and then arms 12q and 17p 15 . Alterations in PLAG1 and MYC, coded on chromosome 8, have been associated with cxpa [16][17][18] .…”
Section: Discussionmentioning
confidence: 99%
“…Studies have suggested that cxpa follows a multistep model of carcinogenesis, with progressive loss of heterozygosity at chromosomal arm 8q, and then arms 12q and 17p 15 . Alterations in PLAG1 and MYC, coded on chromosome 8, have been associated with cxpa [16][17][18] .…”
Section: Discussionmentioning
confidence: 99%
“…Weber and co-workers analyzed TP53 mutations by direct sequencing of exons 4-9 and detected mutations in 4/42 PA and 3/12 myoepitheliomas [14]. Despite the evidence that TP53 might be altered in SGN [10,13,14,16,17,18], we sequenced all of our samples and found only four missense mutations, one nonsense TP53 mutation and a very low frequency of LOH at the 17p 13.1 region in our subset of salivary tumor samples.…”
Section: Discussionmentioning
confidence: 99%
“…These previous papers relied on different techniques (SSCP, for example, which misses mutations when compared to direct sequencing), and in some of them, sequencing was only performed on a few samples. In salivary gland neoplasms, LOH at the TP53 locus has also been reported, mainly in malignant salivary neoplasms or based on visual comparison of the intensity of the alleles [15,16,17,18]. It is important to note that some TP53 mutations do not result in positive immunostaining.…”
Section: Introductionmentioning
confidence: 99%
“…There is ample molecular evidence for a clonal relation in CSs arising in the uterine corpus and this pattern has increasingly been demonstrated in CS of other organs [30,31]. The literature on this topic regarding CS of salivary glands is scarce, but there is mounting evidence that a clonal relation between the carcinomatous and sarcomatous components also hold true in the salivary glands [32][33][34][35]. Speculatively, but in line with current thinking regarding tumorigenesis, the difference between the two categories of CS would then be that the malignant transformation in (1) occurs in a neoplastic, albeit benign, cell in contrast to an uncommitted stem cell in (2), which then through ''genetic instability'' gives rise to two or more lines of differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…A few points of interest are: (1) Frequent loss of 17p (where TP53 is located) has been reported [34] and (2) both overexpression of p53 and TP53 mutations have been reported [27,39]. However, the relation between immunohistochemically detected p53 and the presence of mutation is not simple.…”
Section: Discussionmentioning
confidence: 99%